2017
DOI: 10.1186/s12879-017-2853-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and drug susceptibility testing of mycobacterial isolates from population-based tuberculosis prevalence survey in Ghana

Abstract: Background Mycobacterium tuberculosis complex (MTBC) and Non-tuberculosis Mycobacterium (NTM) infections differ clinically, making rapid identification and drug susceptibility testing (DST) very critical for infection control and drug therapy. This study aims to use World Health Organization (WHO) approved line probe assay (LPA) to differentiate mycobacterial isolates obtained from tuberculosis (TB) prevalence survey in Ghana and to determine their drug resistance patterns.MethodsA retrospective study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 16 publications
8
26
2
Order By: Relevance
“…15,16 The occurrence of 531 mutations (11.7%) in this study was comparable to 9.4% found in the previous study. 10 Our finding and those of Burkina Faso neighboring countries 11,[12][13][14] contrast enormously with the results of numerous studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] which reported higher rates of mutations at 531. High rates of 531 mutations were particularly found in Kyrgyzstan, Ethiopia, Brasil, South West Ethiopia, Georgia, Taiwan and Samara in Russia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…15,16 The occurrence of 531 mutations (11.7%) in this study was comparable to 9.4% found in the previous study. 10 Our finding and those of Burkina Faso neighboring countries 11,[12][13][14] contrast enormously with the results of numerous studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] which reported higher rates of mutations at 531. High rates of 531 mutations were particularly found in Kyrgyzstan, Ethiopia, Brasil, South West Ethiopia, Georgia, Taiwan and Samara in Russia.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, the frequency of rpoB531 mutations is much lower in RMPresistant strains in China where the frequency of the Beijing genotype strains is high. 31 The occurrence of mutation at 526 reported in the current study is higher than rate found in Burkina Faso neighbouring Countries, 11,[12][13][14] lower than the value reported in Nigeria 6 and similar to findings reported from India and Kyrgyzstan. 2,21 All this indicates that mutations at codons 531, 526 and 516 are common, with a varied occurrence across the geographical areas.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A report from central Ethiopia also in line with our nding that no gain of any mutant band was identi ed for the non-hybridized WT8 probe [21]. Similar ndings were also reported for the absence of MUT band from other countries [36,37]. Despite such reports, there were research ndings where gain of MUT probes was identi ed in a part of the rpoB gene [17].…”
Section: Frequency Of Gene Mutations Associated With Rifampicin and Isupporting
confidence: 87%
“…tuberculosis complex isolated followed by M . africanum accounting for 73% to 97.6% and 2.4% to 23% of samples respectively [4245]. M .…”
Section: Discussionmentioning
confidence: 99%